Consumer Preference toward Credit Cards in Kathmandu - Binadi, Mina (Nepalese Journal of Management, 2024)
This study examines the consumer preference toward credit card in Kathmandu. Consumer preference toward credit card is the dependent variable. The selected independent variables are social influences, credit limit and cost, perceived ease of use, risk and benefits. The primary sources of data is used to assess the opinions of respondents regarding social influences, credit limit and cost, perceived ease of use, risk, benefits and consumer preference toward credit card. The study is based on the primary data of 150 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of consumer preference toward credit cards in Kathmandu. The study showed a positive impact of social influence on consumer preference toward credit card. It indicates that higher the level of social influence leads to increase in consumer preference towards credit card. However, the study showed a negative impact of credit limit and cost on consumer preference toward credit card. It indicates that higher the credit limit and cost, lower would be the consumer preference towards credit card. In contrast, the study showed a positive impact of perceived ease of use on consumer preference toward credit card. It indicates that easiness in using credit card leads to increase in consumer preference towards credit card. Likewise, the study showed a negative impact of risk on consumer preference towards credit card. It indicates that higher the risk in using of credit cards, lower would be the consumer preference toward credit card. Further, the study showed a positive impact of benefits on consumer preference toward credit card. It indicates that higher the level of benefits, higher would be the consumer preference towards credit card.